Molecular evolution and functional characterization of the orexigenic peptide 26RFa and its receptor in vertebrates - Ukena, Kazuyoshi; Vaudry, Hubert; Leprince, Jérôme; Tsutsui, Kazuyoshi (Cell and tissue research, 2011)
Several neuropeptides possessing the RFamide motif at their C-termini (designated RFamide peptides) have been characterized in the hypothalamus of a variety of vertebrates. To date, five groups of the RFamide peptide family have been shown to exert several important neuroendocrine, behavioral, sensory, and autonomic functions. Since the discovery of the 26-amino acid RFamide peptide (termed 26RFa) from the frog brain, 26RFa has been shown to exert orexigenic activity in mammals and to be a ligand of the previously identified orphan G-protein-coupled receptor GPR103. Recently, 26RFa and its cognate receptor GPR103 have been identified in the brain of birds. This mini-review summarizes the advances in the identification, localization, and functions of 26RFa and its cognate receptor GPR103 in vertebrates and highlights recent progress made in birds.